The effectiveness of three different recovery methods on blood lactate, acute muscle performance, and delayed-onset muscle soreness: a randomized comparative study - (:unkn) unknown (EDIZIONI MINERVA MEDICA, 2020)
BACKGROUND: Recovery from exercise is important in sports and rehabilitation for preventing exercise-induced injuries and recovery of performance. This study aimed to compare active recovery (AR), neuromuscular electrical stimulation (NMES), and foam rolling (FR) in terms of blood lactate (Bla) removal, reduction in delayed-onset muscle soreness (DOMS), and restoration of muscle strength, endurance, and flexibility in healthy young individuals. METHODS: Forty-five subjects aged 20-25 years were assigned to AR, FR, and NMES groups. The subjects performed a single bout of circuitbased high-intensity training (CBHIT) at 85% of the heart rate reserve (HRR). The subjects in the AR group walked at 40% of the HRR, whereas those in the FR group self-massaged the tight muscles. In the NMES group, electrical stimulation was applied to the hamstrings and quadriceps. All recovery methods took 15 minutes. The sit-and-reach performance, quadriceps and hamstring strength, and squat endurance of the subjects were measured prior to CBHIT and after recovery. Bla concentrations were measured before CBHIT and at 0, 5, and 20 minutes of recovery. The DOMS were evaluated for 3 days. RESULTS: After recovery, no significant differences were found between the groups in terms of quadriceps (right, P=0.82; left, P=0.772) and hamstring (right, P=0.41; left, P=0.30) strength, sit-and-reach performance (P=0.55), squat endurance (P=0.18), Bla concentration at each time point (P=0.94), and DOMS (P=0.31). CONCLUSIONS: This study showed that AR, NMES, and FR have similar effects on Bla removal, performance recovery, and DOMS reduction in healthy young individuals.
Keywords: Recovery of function; Electrical stimulation; Myofascial pain syndromes; NEUROMUSCULAR ELECTRICAL-STIMULATION; ACTIVE RECOVERY; CROSS-OVER; EXERCISE; MOTION; RANGE; RELIABILITY; STRATEGIES; VALIDITY; MASSAGE